Survival and adverse events in patients with atrial fibrillation at left ventricular assist device implantation: an analysis of the European Registry for Patients with Mechanical Circulatory Support. (24th January 2022) - Antonides, Christiaan F J; Yalcin, Yunus C; Veen, Kevin M; Muslem, Rahatullah; De By, Theo M M H; Bogers, Ad J J C; Gustafsson, Finn; Caliskan, Kadir
Abstract: OBJECTIVES: Atrial fibrillation (AF) is a risk factor for mortality and cerebrovascular accidents (CVAs) and is common in patients with heart failure. This study evaluated survival and adverse events in patients with a left ventricular assist device (LVAD) and a history of AF in the European Registry for Patients with Mechanical Circulatory Support. METHODS: Patients with a continuous-flow LVAD, AF or sinus rhythm (SR) and a follow-up were included. Kaplan–Meier analyses for survival (including a propensity-scored matched analysis), freedom from CVA, pump thrombosis, bleeding and a composite of pump thrombosis/CVA were performed. To correct for covariate imbalance, a Kaplan-Meier (KM) analysis was performed after propensity score (PS) matching the groups. Finally, a Cox regression was performed for predictors of lower survival. RESULTS: Overall, 1821 patients (83% male) were included, with a median age of 57 years and a median follow-up of 13.1 months (interquartile range: 4.3–27.7). Preoperative Electrocardiogram (ECG) rhythm was AF in 421 (23.1%) and SR in 1400 (76.9%) patients. Patients with pre-LVAD AF had a lower ≤90-day (81.9% vs 87.1%, P = 0.0047) and 4-year (35.4% vs 44.2%, P = 0.0083) survival compared to SR. KM analysis with PS matching groups revealed a trend ( P = 0.087) towards decreased survival. Univariable analyses confirmed pre-LVAD AF as a predictor for mortality, but the multivariable analysis did not. No difference in the rate of adverse events was found. An analysis of patients at 24 months revealed a higher rate of CVAs for pre-LVAD AF patients (77% vs 94.3%, P < 0.0001). CONCLUSIONS: Patients with pre-LVAD AF undergoing LVAD implantation had a worse survival. However, after performing a multivariate analysis, and PS matching analysis, AF was no longer significant, indicating a worser preoperative condition in these patients. Concerning thrombo-embolic events, only patients with pre-LVAD AF alive beyond 24 months have a higher risk of CVAs. Abstract : Left ventricular assist devices (LVADs) have become an accepted treatment modality in patients with end-stage heart failure (HF) [1].